First in vivo evaluation of a flexible self‐apposing left atrial appendage closure device in the canine model. Issue 1 (2nd June 2015) - Cheng, Yanping; Conditt, Gerard; Yi, Genghua; Tellez, Armando; Corcoran, Michael; Rousselle, Serge; Kaluza, Greg L.; Granada, Juan F.
<x xml:space="preserve">Abstract</x> Objectives Aimed to evaluate the feasibility of deployment and healing response of a novel transcatheter left atrial appendage (LAA) occlusion device in the canine model Background LAA occlusion is proposed to reduce the risk of stroke in atrial fibrillation patients Methods Transseptal puncture and device deployment was guided under fluoroscopy and transesophageal echocardiography (TEE) in five dogs. First, a distal cylindrical bulb occluder was released and secured to the appendage wall with hooks. Subsequently, a proximal sail was unfolded, covering the LAA ostium. Rotational angiography, TEE, and histology outcomes were assessed 30 days following implantation Results Pre‐operative TEE revealed the mean diameter of the LAA ostium to be 17.2 ± 1.6 mm with a depth of 18.5 ± 1.7 mm. The landing zone for the distal bulb was measured to be 12.8 ± 1.3 mm. The mean bulb diameter at implant was 16.8 ± 1.8 mm. Post‐operative TEE showed adequate positioning and successful LAA occlusion with all implanted devices. Pericardial effusion requiring pericardiocentesis was seen in one animal following device implantation. At 30 days, TEE revealed full occlusion of all LAA ostia with the exception of a minimal peri‐device leak (<3 mm) observed in one animal. No pericardial effusion or device‐related thrombus formation was found at termination. Histological analysis confirmed circumferential occlusion of all appendages and complete neointimal coverage on the luminal aspect of the occluder Conclusion The percutaneous delivery of a novel self‐positioning LAA occlusion device is feasible and safe in a canine model. At 30 days, all devices displayed complete healing and occlusion of the LAA without any device related adverse events. © 2015 Wiley Periodicals, Inc.